2008
DOI: 10.22358/jafs/66474/2008
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus test and comet assay on mice fed over five generations a diet containing genetically modified triticale

Abstract: One of the concerns regarding the common use of genetically modifi ed (GM) feed in animal nutrition is that transgenic sequences may have a negative effect on the organism or (and) its cells. The present report assesses the genotoxic potential effect of a diet containing GM triticale on mice by using micronuclei test and comet assay. One group of mice (C57 Bl/6J strain) were fed continuously over fi ve generations a pelleted diet containing 20% of GM triticale (tolerant to phosphinothricine) grain, while the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…A 105-day feeding study supporting this finding was with mice which were fed with GM soybean and no histopathological abnormalities in the spleen and mucosa of small intestine were detected (Teshima et al, 2000). Results obtained by Jaszczak et al (2008) did not reveal any difference in DNA damage between the control and experimental groups of mice fed a GM diet over 5 generations. In contrast to this study, another feeding study in rats with MON 863 Bt-corn demonstrated no histopathological damage in spleen and liver (Smith, 2005).…”
Section: Discussionsupporting
confidence: 58%
“…A 105-day feeding study supporting this finding was with mice which were fed with GM soybean and no histopathological abnormalities in the spleen and mucosa of small intestine were detected (Teshima et al, 2000). Results obtained by Jaszczak et al (2008) did not reveal any difference in DNA damage between the control and experimental groups of mice fed a GM diet over 5 generations. In contrast to this study, another feeding study in rats with MON 863 Bt-corn demonstrated no histopathological damage in spleen and liver (Smith, 2005).…”
Section: Discussionsupporting
confidence: 58%
“…Very limited studies have been conducted to investigate the genotoxicity of diets containing genetically modified plants. Results obtained by Jaszczak et al (2008) did not reveal any difference in DNA damage between the control and experimental groups of mice fed a GM diet over 5 generations. Contrary to Jaszczak et al (2008), in our investigation, the relative ratio of DNA fragmentation results revealed a higher ratio of DNA breaks in the liver cells of GM-fed rats.…”
Section: Discussionmentioning
confidence: 72%
“…No adverse effects were reported (Rhee et al, 2005) on the reproductivedevelopmental ability of rats fed 5% GM potatoes for 5 generations. A diet containing 20% GM triticale (Jaszczak et al, 2008) did not induce chromosomal damage. No apparent adverse effect was also reported (Sakamoto et al, 2008) in rats fed on GM soy at a level of 30% in the diet for 104 weeks.…”
Section: Discussionmentioning
confidence: 80%
“…is was the starting point for many studies, not only on genetic transformation but also on the potential negative impact of transgenic cereal plants on the environment. ese studies were carried out in various Polish laboratories aer 2000, and among many others, included a project on feeding successive generations of experimental mice with transgenic triticale (Baranowski et al, 2006;Jaszczak et al, 2008;Krzyżowska et al, 2010). e latter was conducted by IHAR in cooperation with the Institute of Genetics and Animal Biotechnology, Polish Academy of Sciences, Jastrzębiec and with the Faculty of Veterinary Medicine, Warsaw University of Life Sciences -SGGW.…”
Section: Multi-generation Analysis Of Transgenic Triticale Plantsmentioning
confidence: 99%